With God on One's Side: The Social Geometry of Death Row Apologies1. Issue 1 (6th March 2013) - Cooney, Mark; Phillips, Scott
<x xml:space="preserve">Abstract</x> Apology is an increasingly prominent form of conflict management in many areas of social life. Yet there are few systematic studies of apology as a dependent variable. Analyzing the last statements of Texas death row prisoners, we find that the best predictor of apology is affiliation with God. Under traditional Western conceptions, God is an actor endowed with extraordinarily high status. Drawing on the theoretical paradigm known as pure sociology, we argue that death row prisoners who invoke God as a third party in their conflict thereby elevate their own status. Greater vertical closeness to the victim's side generates more social assertiveness and a greater willingness to apologize publicly. In addition, affiliation increases prisoners' relational closeness to God, enhancing their probability of adopting God's modern message of reconciliation. God's status has, however, declined somewhat over the past several centuries—a trend that helps to explain the modern religious emphasis on reconciliation over punishment, apology over defiance.